Variation of Seed Components According to Sowing Date and Variety of Sprout Soybean in the Mid-Northern Region in Korea. (29th May 2020) - Park, Chang Hwan; Shin, Dong Sun; Kim, Namgeol; Choi, Induck; Choi, Hyesun; Park, Ji Young; Lee, Seuk Ki; Jeong, Kwang-Ho
Abstract: Objectives: Soybean( Glycine max L.) sprouts are widely used in Korea as main and sub materials in various dishes such as stew, 'Bibimbap', 'Haejangguk', and seasoned bean sprouts. The purpose of this study was to investigate the variations of general compositions and antioxidant properties in sprout soybean seed according to varieties and sowing dates in the central region of Korea, and to utilize the basic data for stable supply of raw soybeans in response to the changes in production environment. Methods: Sprout soybean were produced from the experimental field of Department of Central Area Crop Science of the National Institute of Crop Science (NICS), located in Suwon, Gyeonggi-do. The sowing dates were on June 30 th, July 10 th and July 20 th in 2018 respectively. Planting and cultivation were followed by standard soybean cultivation methods of NICS. The harvested raw sprout soybean seeds at each seeding time were ground for the general compositions analysis. Antioxidant capacity was measured with total polyphenol contents and DPPH and ABTS radical scavenging activity. Results: Approximate compositions of sprout soybean seed showed significant differences according to varieties and sowing date. Moisture, crude fat, and crude protein were the highest in the first sowing date, and tended to decrease in most varieties as the seeding time was delayed, whereas carbohydrate content increased at late sowing time. DPPH radical scavenging activity showed the highest tendency in second seeding. ABTS radical scavenging activity decreased as the seeding time was delayed in the most varieties, but 'Soyeon' and 'Aram' increased in second seeding. Conclusions: Taken the above results together, the significant differences in the approximate compositions and antioxidant capacities recognized due to varieties and sowing dates. Therefore, it was considered that the selection of proper varieties and sowing date should be considered carefully when growing raw sprout soybean grains in the central region in Korea. Funding Sources: This study was supported by the RDA Agenda Project (project number: PJ01251603).